Laser-induced florescence and absorption studies on some food colors and flavors by violet diode lasers - Kazi Monowar Abedin; Khadija Saleh Al Sawafi (Results in Optics)
Laser-induced fluorescence (LIF) of nine food colors and flavors (Allura red, Sunest Yellow, Brilliant blue, green color (2 types), orange color, coffee, strawberry and pistachio flavor) have been studied using a compact violet laser operating at 405 nm. The same materials have also been studied by absorption spectroscopy in the visible region. The LIF and absorption spectroscopy provide complimentary information in the study of the molecular constituents of these materials. The spectral features of each color and flavors were identified and correlated with the molecular structure of the important constituents. Dependence of the fluorescence intensity of some food colors with the viscosity of the solvent was observed, this may have applications in monitoring food quality, with food colors serving as a fluorescent probe.